Bridging the policy divide in Nigeria: Cross-sectoral Collaboration, Accountability, and Data Integration for Sustainable Education Governance - Jennifer Iloakasia, Adaobi (Magister’s Program in Islamic Education Postgraduate Program, Universitas Annuqayah Sumenep, 2025)
Weak organizational and institutional structures continue to constrain education governance in developing contexts, hindering the achievement of sustainability goals. This study investigated whether cross-sectoral collaboration, accountability, and data integration significantly predict sustainable education governance in Nigeria. A correlational survey design was employed, involving education policy makers, government administrators, and civil society actors at the federal, state, and local levels. A sample of 178 respondents was randomly selected through stratified sampling to represent the three tiers of governance. Data were collected using a structured, validated questionnaire and analyzed through Spearman's Rank-Order Correlation and multiple regression. Results showed a moderate positive bivariate correlation between cross-sectoral collaboration and governance (r = .453, p = .000); however, this contribution became non-significant once accountability and data integration were controlled for (β = –.044, p = .222), likely due to shared explanatory overlap among predictors. The overall regression model was significant, F(3,174) = 331.111, p = .000, explaining 85.1% of the variance (R² = .851, R = .922). Accountability (β = .850, p = .000) and data integration (β = .150, p = .000) were significant predictors, with accountability showing the strongest influence. The study concludes that accountability and data integration are the most critical drivers of sustainable education governance, while cross-sectoral collaboration contributes meaningfully only when considered independently. It is recommended that stakeholders strengthen accountability mechanisms, integrate education data systems, and institutionalize cross-sectoral coordination to improve governance outcomes in Nigeria.